Caries treatment in a dental practice‐based research network: movement toward stated evidence‐based treatment. Issue 2 (5th October 2012) - Gilbert, Gregg H.; Gordan, Valeria V.; Funkhouser, Ellen M.; Rindal, D. Brad; Fellows, Jeffrey L.; Qvist, Vibeke; Anderson, Gerald; Worley, Donald; ,
Abstract Objectives Practice‐based research networks (PBRNs) provide a venue to foster evidence‐based care. We tested the hypothesis that a higher level of participation in a dental PBRN is associated with greater stated change toward evidence‐based practice. Methods A total of 565 dental PBRN practitioner‐investigators completed a baseline questionnaire entitled 'Assessment of Caries Diagnosis and Treatment'; 405 of these also completed a follow‐up questionnaire about treatment of caries and existing restorations. Certain questions (six treatment scenarios) were repeated at follow‐up a mean (SD) of 36.0 (3.8) months later. A total of 224 were 'full participants' (enrolled in clinical studies and attended at least one network meeting); 181 were 'partial participants' (did not meet 'full' criteria). Results From 10% to 62% of practitioners were 'surgically invasive' at baseline, depending on the clinical scenario. Stated treatment approach was significantly less invasive at follow‐up for four of six items. Change was greater among full participants and those with a more‐invasive approach at baseline, with an overall pattern of movement away from the extremes. Conclusions These results are consistent with a preliminary conclusion that network participation fostered movement of scientific evidence into routine practice. PBRNs may foster movement of evidence into everyday practice as practitioners become engaged in the scientific process.